非圆齿轮的动力学特性研究 - 张爱梅; 蒋佳; 魏丽君; 赵娟; 王雷 (Jixie chuandong)
From the basic mechanics principle and combining the universal clylindrical spur gear’s meshing mechanism,the general dynamics model of non-circular gear is derived and the discussion to the model’s solution is carried out. It is usefull for the developing towards the direction of high speed and heavy load.